KENALI dan HENTIKAN BULLYING DI SEKOLAH : (Pengenalan Sekolah Bagi Siswa Baru SMK dan SMPTK Jimero Kota Sorong) - Ohoiwutun, Koorneles (SOLIDEO Jurnal Pengabdian Masyarakat, 2025)
The purpose of this activity is to provide in-depth understanding for new students entering junior high and high schools, so that they can recognize, prevent and eliminate the problem of bullying in the environment where they are, both in the school environment, family environment, and in the community. In the implementation in the field, it turned out that many students already knew about the problem of bullying so that it was very easy to convey this material so that the implementation of the socialization ran smoothly, orderly and enjoyable because students gained new knowledge about preventing the problem of bullying in the environment where they study.